The Decision Problem for Standard Classes - Gurevich, Yuri (Journal of Symbolic Logic, 1976)
The classification of prefix-signature fragments of (first-order) predicate logic with equality, completed in [7], is extended to first-order logic with equality and functions. One case was solved (confirming a conjecture of this author) by Saharon Shelah.